1983
DOI: 10.1038/bjc.1983.101
|View full text |Cite
|
Sign up to set email alerts
|

The association of cytosol oestrogen and progesterone receptors with histological features of breast cancer and early recurrence of disease

Abstract: Summary Two hundred and eighty-eight primary breast tumours were examined for the presence or absence of oestrogen (RE,)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
18
0
7

Year Published

1985
1985
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(27 citation statements)
references
References 46 publications
2
18
0
7
Order By: Relevance
“…Thus, because of their internal correlations in multivariate analysis, the prognostic value of many of these parameters fades away (9,10).…”
mentioning
confidence: 99%
“…Thus, because of their internal correlations in multivariate analysis, the prognostic value of many of these parameters fades away (9,10).…”
mentioning
confidence: 99%
“…In an effort to explain this, and perhaps also improve selection of these patients, the association between oestrogen receptors and a variety of other biological parameters has been investigated, e.g. cell cycle kinetics (Meyer et al, 1984), histological tumour typing and grading (Howat et al, 1983;Mossler et al, 1980;Underwood, 1983) and nuclear ploidy. In general, these studies have shown that variables associated with poor prognosis in breast cancer appear to be associated more frequently with an absence of oestrogen receptors.…”
mentioning
confidence: 99%
“…[12][13][14] It seems that if Accepted for publication 24 July 1986 patients with oestrogen receptor positive tumours develop distant metastases they do so later than patients with oestrogen receptor negative tumours, but that the prognosis in the end is the same in both groups of patients.…”
mentioning
confidence: 99%